A Review of Antibiotic Prophylaxis for Post-operative Endophthalmitis - Apurva Goray; Supriya Arora; Divya Yadava; Shantanu Gupta; Basudeb Ghosh (Delhi Journal of Ophthalmology)
The purpose of this review is to summarise all available evidence regarding antibiotic prophylaxis for post cataract surgery endophthalmitis as some prophylactic measures add significantly to the cost of surgery, are routinely used and yet their benefit to cataract patients has not been proven. Use of Povidone Iodine before starting the surgery is one of the most effective means of reducing the incidence of postoperative endophthalmitis. Intracameral cefuroxime is another important measure advocated by many studies. Intracameral moxifloxacin may be considered as an alternative to cefuroxime. Although pre and post-operative systemic or topical antibiotics, subconjunctival antibiotics and antibiotics in the irrigating solution have not been proven to decrease post-operative endophthalmitis, they have not been shown to be detrimental and hence surgeons may consider their use according to personal preferences and a cost-benefit analysis of their healthcare system.